2009
DOI: 10.1002/lary.20576
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surveillance on survival after laryngeal cancer in the medicare population

Abstract: More frequent surveillance visits was not associated with a survival advantage in the overall population. Patients with glottic cancer had a postrecurrence survival advantage if seen during the surveillance period. Laryngeal cancer patients had better postrecurrence survival than other head and neck sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…Studies have examined the impact of surveillance office visits and have concluded that survival is not related to the intensity of follow‐up . Nonetheless, the NCCN guidelines recommend office visits for cancer survivors that decrease in frequency over time.…”
Section: Recommendationsmentioning
confidence: 99%
“…Studies have examined the impact of surveillance office visits and have concluded that survival is not related to the intensity of follow‐up . Nonetheless, the NCCN guidelines recommend office visits for cancer survivors that decrease in frequency over time.…”
Section: Recommendationsmentioning
confidence: 99%
“…Because of the anatomy of the head and neck, self‐surveillance can be difficult, emphasizing the importance of active surveillance by a trained physician. Active surveillance may allow for earlier detection of asymptomatic recurrence or second primary lesions, which may increase the success of treatment . As well, treatment of HNC can result significant late functional sequelae, and regular follow‐up provides patient access to specialized rehabilitative services, essential for optimizing outcomes in cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor recurrence is relatively common in all stage groups regardless of the primary treatment. Recurrence is detected in 16% to 29% of patients with laryngeal SCC, with large variability between different subsites and stages . When laryngeal SCC recurs, salvage of limited recurrences may be attempted with organ‐sparing surgery .…”
Section: Introductionmentioning
confidence: 99%